The evolving landscape of brain metastasis - Valiente, Manuel; Ahluwalia, Manmeet S.; Boire, Adrienne; Brastianos, Priscilla K.; Goldberg, Sarah B.; Lee, Eudocia Q.; Le Rhun, Emilie; Preusser, Matthias; Winkler, Frank; Soffietti, Riccardo (Trends in cancer, 2018)
Metastasis, involving the spread of systemic cancer to the brain, results in neurologic disability and death. Current treatments are largely palliative in nature; improved therapeutic approaches represent an unmet clinical need. However, recent experimental and clinical advances challenge the bleak longterm outcome of this disease. Encompassing key recent findings in epidemiology, genetics, microenvironment, leptomeningeal disease, neurocognition, targeted therapy, immunotherapy, and prophylaxis, we review preclinical and clinical studies to provide a comprehensive picture of contemporary research and the management of secondary brain tumors.
Gesehen am 03.03.2020
Published online: 2019 July 01